(The Ethics of) Teaching Science and Ethics: A Collaborative Proposal - William P. Kabasenche (American Society for Microbiology, 2014)
I offer a normative argument for a collaborative approach to teaching ethical issues in the sciences. Teaching science ethics requires expertise in at least two knowledge domains—the relevant science(s) and philosophical ethics. Accomplishing the aims of ethics education, while ensuring that science ethics discussions remain grounded in the best empirical science, can generally best be done through collaboration between a scientist and an ethicist. Ethics as a discipline is in danger of being misrepresented or distorted if presented by someone who lacks appropriate disciplinary training and experience. While there are exceptions, I take philosophy to be the most appropriate disciplinary domain in which to gain training in ethics teaching. Science students, who must be prepared to engage with many science ethics issues, are poorly served if their education includes a misrepresentation of ethics or specific issues. Students are less well prepared to engage specific issues in science ethics if they lack an appreciation of the resources the discipline of ethics provides. My collaborative proposal looks at a variety of ways scientists and ethicists might collaborate in the classroom to foster good science ethics education.